Timing of Tocilizumab Administration Under the Guidance of IL-6 in CAR-T Therapy for R/R Acute Lymphoblastic Leukemia - Zhang, Yinqiang; Zhou, Fen; Wu, Zhuolin; Li, Yingnan; Li, Chenggong; Du, Mengyi; Luo, Wenjing; Kou, Haiming; Lu, Cong; Mei, Heng (Frontiers in Immunology, 2022)
Chimeric antigen receptor T (CAR-T) cells targeting CD19 have achieved great clinical responses in patients with relapsed or refractory (R/R) acute B lymphoblastic leukemia. However, severe adverse events such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome restrict it to further application. Tocilizumab is the corner stone for the treatment of severe CRS. It has been used to treat mild CRS in recent years, whereas some statistical supports clarifying the suitable timing of its administration are lacking. Sixty-seven patients with B-cell acute lymphoblastic leukemia (B-ALL) were treated with CD19-CART and enrolled in the study, of which 33 patients received Tocilizumab. Application of Tocilizumab in patients with grade 2 CRS in American Society for Transplantation and Cellular Therapy (ASTCT) criteria can significantly shorten the duration of CRS without affecting side effects and long-term efficacy. However, a number of patients still developed severe CRS with early use of Tocilizumab, indicating the significance of the introduction of clinical laboratories to assist medications. Statistically, patients with less than fourfold increase in IL-6 levels had a higher incidence of severe CRS after receiving Tocilizumab (37.5% versus. 0%, p=0.0125), which provided a basis for refining CRS intervention strategies under the guidance of IL-6. Clinical Trial Registration www.clinicaltrials.gov, NCT02965092 and NCT04008251